An overview of retinal blood vessels segmentation - Jusoh , Fatimatufaridah; Haron , Habibollah; Ibrahim , Roliana; Che Azemin, Mohd Zulfaezal (Springer International Publishing, 2016)
In the recent past, the application of image processing in the fields of medicine and ophthalmology was widely used. Retina blood vessels are the only part of the human body that can be directly visualized non-invasively in vivo. Retina segmentation is important to help ophthalmologists detect various eyes diseases such as diabetic retinopathy, glaucoma, and age macular degeneration. Consequently, vessel segmentation is an important step in image analysis used to assess retinal abnormality. Vessel segmentation must be completed accurately to obtain good results for further image analysis. This paper reviews the algorithms used in previous studies on retinal vessel segmentation and discusses the problems associated with retina analysis.